Electric discharge coating on graphite using W–Cu sintered tool. (4th March 2022) - Mazarbhuiya, Rashed Mustafa; Rahang, Maneswar
ABSTRACT: This article describes about the modification of graphite surface by depositing a hard layer of tungsten (W) and copper (Cu) material using electrical discharge machining (EDM) setup in reverse polarity. The sintered tool is prepared by heating a Powder Metallurgical (P/M) green compact of 75%W-25%Cu at 900 0 C in an argon atmosphere. The deposited layer is studied by evaluating the Tool Wear Rate (TWR), Material Deposition Rate (MDR), and Surface Roughness (Ra). The coating is characterized by FESEM, EDS, and XRD analyses. The existence of tool particles (W and Cu) and carbides of tungsten (WC and W2 C) are witnessed on the graphite surface. The tool materials are impinged up to 19.93 µm of depth from the surface level. The experimental results show an increase in thickness of the coating with increased peak current settings. Minimum thickness of 15.46 µm and maximum thickness of 33.93 µm are found in the experimentation.